Pelatihan Pelayanan Keluarga Bagi Tim LIFE Sorowako - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Devotion: Jurnal Pengabdian Masyarakat, 2026)
The purpose of this study is to demonstrate the critical need, importance, and strategic nature of Christian marriage preparation, marriage ministry, and family development services for every individual, every church, and every ministry organization that places a strong emphasis on marriage and family. The urgent need for Christian marriage and family development is supported by various reasons and facts, some of which are presented in the introduction. Therefore, competent, called, and caring individuals are needed to be trained and equipped to actively participate in Christian family development services. This Family Ministry Training for the LIFE Sorowako Team serves as an example and role model for efficient and effective development to be implemented and continued by other churches and ministry institutions. The research method used was a qualitative literature study approach and descriptive analysis of the training process. The results of this study demonstrate the importance of ToT (Training of Mentors) for family ministry trainers and coaches to develop and enhance quality Christian marriages and families.